Die Wiener Hochschule für Welthandel und ihre Professoren 1938-1945 - Berger, Peter (Österreichische Zeitschrift für Geschichtswissenschaften, 1999)
In 1898 a specialized commercial school ("Exportakademie") was established in Vienna to promote the Habsburg Monarchy's foreign trade with southeastern Europe and the Levant area. Renamed into "Hochschule für Welthandel" (HWH), the institution was granted university status in 1930 and, during the economic depression of the thirties, became a hotbed of acadeemic pan-germanism and antisemitism. The fact that (Jewish) private business had an important say in the managemcnt of the HWH could not prevent repeated acts of violence of Nazi students against their Jewish and foreign colleagues, but it put an effective brake on some professors' inclinations to openly side with the pan-German cause. After the "Anschluß" in March 1938 thc HWH faculty was purged of its members considered foes of National Socialism, and of Jews. (This affected only the staff of lecturers, as no Jew held a regular professorship in 1938.) Among those forced to retire were two renowned cconomists who bad helped to formulate austro-fascist and corporatist doctrines, Walter Heinrich and Richard Kerschagl. Both were rcinstalled as professors after the Second World War. The German Ministry of Education, which took full responsibility for the HWH in February 1940, first consiclered of shutting it down altogether, then tried to merge it with the much bigger University of Vienna. Both plans were dropped, howevcr, and the HWH was allowcd to prove its value for Germany's imperialistic ambitions. With the financial aid of German industry, it set up an ambitious training programme for future "merchants into the East", who were expected to replace the Jews in East European trade.